Determination of serum Zinc level in diarrhea children - AR Firouz Jahi (Babol University of Medical Sciences, 2004)
Background and Objective: Zinc is an essential trace element for humans that has important role in the immune system. Zinc deficiency contributes to the incidence, prevalence, severity and duration of infectious diarrhea and FTT (Failure to Thrive). This study was done to determine the zinc level in hospitalized diarrhea children. Methods: This study was conducted on 100 diarrhea children who were hospitalized in Amirkola pediatric hospital during June and July 2001. Characteristics such as age, gender, duration of diarrhea, serum zinc level and FTT were studied. Data were analyzed by X² test, Fisher’s exact tests and Spearman correlation coefficient. Findings: From 100 patients, 42 were female and 58 were male that their range of ages was from 2 months to 12 years and the mean age was 45.9 months. The mean serum zinc level was 105.8 µg/dl. It was seen a significant difference between growth percentile and serum zinc level (P=0.012, Spearman correlation coefficient=0.25). Children with low serum zinc levels (<63.8 µg/dl) spent a significantly greater number of days with diarrhea. In addition, incidence of diarrhea and zinc deficiency in the children bellow 6 years was greater than other group’s ages. Conclusion: According to the results of this study, patients with zinc deficiency had longer duration of diarrhea and the children with FTT had low serum zinc level.